Symmetric deliberative management transition model: from Habermas deliberative democracy to mediation matrix. ACESF case study. - Courie, May; Meier, Olivier (International Transitions, 2024)
Societal transition refers to large-scale changes in the social, economic, political and cultural structures of a society. These transitions often occur in response to internal dynamics, external pressures, where power asymmetries between stakeholders a¤ect the outcomes in transition management contexts and deliberative processes are needed. However democratic processes into transition management frameworks are still underdeveloped. We propose a methodology to address this gap. By focusing on a cultural and educational intermediary organisation between China and France, we operationalise Habermas’ pillars of deliberative democracy, thus establishing a metasystem of mediation practices with corresponding mechanisms and propose a mediation session configuration strategy for a symmetric deliberative management transition model. A systemic methodology in multi-actor multi-criteria analysis, in transition management, in intercultural management, in international context.